[PP.35.35]: ANTIHYPERTENSIVE THERAPY IN PATIENTS AFFECTED BY BIPOLAR DISORDERS TREATED WITH LITHIUM. (June 2015) - Bisogni>, V.>; Mareso, S.; Rossitto, G.; Azzolini, M.; Piazza, D.; Maiolino, G.; Cesari, M.; Rossi, G.P.
Abstract : Objective: Bipolar disorders (BD) are severe forms of early onset disability that require chronic treatment with lithium (Li). As Li has a very narrow therapeutic index and it is 95% excreted by the kidney, drugs that alter its renal clearance can increase its serum levels to potentially fatal values. According to Bayes' rule, the probability that bipolar disorders can concur with arterial hypertension ranges between 1.5% and 2.2%. Notwithstandingly, only anecdotal reports exist in literature on use of different antihypertensive drugs in BD patients on chronic Li therapy. The aim of our study was to gather information on how antihypertensive drugs induce "lithium-toxicity". Design and method: We searched the PubMed/MEDLINE databases for reports on the interaction between lithium and antihypertensive drugs using the Population Intervention Comparison Outcome (PICO) strategy. Results: Twenty-three papers published from 1975 through 2013 reported on the adverse effects of co-administration of Li and antihypertensive agents. The possible mechanisms of interaction are resumed in Figure 1. Figure. No caption available. Signs and symptoms of overt Li intoxication occurred with agents that reduce the renal clearance of lithium. They were resolved mostly with withdrawal of the offending antihypertensive drug and forced alkaline diuresis, and with haemodialysis in the most severe cases. Severity of symptoms of Li toxicity showed a direct correlation (p < 0.05) with total daily dose of Li. However, at regression analysis Li toxicity was not predicted by age, baseline serum Li and creatinine levels, nor by any class of antihypertensive drugs. Conclusions: Given the unfeasibility of predicting Li toxicity, strict monitoring of patient's clinical conditions and Li levels is key for early detection of this potentially fatal conditions in hypertensive patients with BD treated with Li and antihypertensive drugs.